GEOCHEMICAL CHARACTERISTICS AND MANTLE SOURCES OF THE OLIGO-MIOCENE PRIMITIVE BASALTS FROM SARDINIA: THE ROLE OF SUBDUCTION COMPONENTS - Franciosi, Luigi; Lustrino, Michele; Melluso, Leone; Morra, Vincenzo; D’Antonio, Massimo (Ofioliti, 2003)
During the Oligo-Miocene, the Island of Sardinia was covered by the products of voluminous magmatic activity, with a typical subduction-related signature. The mafic rocks of the Montresta (north) and Arcuentu (south) volcanic districts include primitive high MgO basalts whose trace element and Sr-, Ndand Pb-isotope compositions constrain the nature and role of subduction-related components in the Tertiary Sardinian volcanism. The geochemical and isotopic data require an approximate degree of partial melting of 15% of a MORB-like depleted mantle prior to enrichment, and the input of two subduction components in the mantle wedge consisting of fluids from subducted oceanic crust (altered MORB) and fluids from subducted sediments. Ratios among trace elements which are variably compatible with fluid and melt phases (i.e. Th/Pb, Th/Nd and Sr/Nd) exclude the contribution of melts from the subducted slab. Models based on isotopic ratios indicate that the pre-subduction depleted mantle source of Sardinia magmas was enriched by 0.1-0.5% MORB fluid and less than 0.1% sediment fluid. The geochemical and isotopic compositions of the Montresta volcanic rocks are homogeneous, whereas those of the Arcuentu show quite heterogeneous characters, suggesting variations in mantle source over the long time-span (about 13 Ma) of volcanic activity in this district.